CHANGING SPECTRUM OF GALLSTONE DISEASE: AN EXPERIENCE OF 23 CASES LESS THAN 10 YEARS OF AGE - Malik, AM; Khan, A; Sheikh, U; Sheikh, S; Laghari, AA; Talpur, KA (Journal of Ayub Medical College Abbottabad, 2008)
Background: An overall increase in the incidence of paediatric cholelithiasis forms the basis of this study, which aims to investigate the overall changing clinical pattern of cholelithiasis. Methods: This is a retrospective observational descriptive study including twenty three (23) patients with gallstones admitted and operated during June 2006-June 2008 in surgical department of a teaching hospital. All the patients with sonological evidence of gallstones, less than 10 years of age with history of acute or chronic abdominal symptoms are included in the study population. After admission all the subjects were investigated and finally operated by open approach (21 patients) during the same admission. The details of all the patients were recorded on a proforma and statistical analysis done on SPSS version 12. Results: Of the total study population, there were 19 (82.6 %) males and 4 (17.39%) females with a mean age of 7 years and a range of 4-10 years. Ultrasound revealed gallstones in all the patients with a varying proportion of the walls of gallbladder. The commonest presentation was abdominal pain in the right upper quadrant, which was vague, and of mild to moderate intensity. In 21 (91.30%) patients, no specific underlying cause was found while two patients (8.6%) had haematological disorder as underlying cause for the gallstones. Conclusion: This study indicates an alarming increase in the incidence of idiopathic gallstones in children less than 10 years of age with a distinct male predominance. Keywords: Cholelithiasis, children, idiopathic gallstones, Haematological disorders.